2005
DOI: 10.5465/amr.2005.16387886
|View full text |Cite
|
Sign up to set email alerts
|

To Act or not to Act: The Dilemma Faced by Sexual Harassment Observers

Abstract: Efforts to end sexual harassment that rely primarily on target reporting are unlikely to be successful because most targets do not report their experiences. Thus, we explore an alternative mechanism for controlling sexual harassment-observer intervention. We examine observer intervention in sexual harassment using the literature on bystander intervention for guidance. We describe the concept of observer intervention, develop a taxonomy of intervention types, and discuss factors promoting and inhibiting its occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
207
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(221 citation statements)
references
References 60 publications
11
207
1
2
Order By: Relevance
“…We show that an important part of third-party endorsement of punishment of the perpetrator resides in the extent to which they take the perspective of those involved in deviant behavior (i.e., the perpetrator or victim). Taking -Kelly, 2005). In this respect, our results likely represent a simplified thirdparty response.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We show that an important part of third-party endorsement of punishment of the perpetrator resides in the extent to which they take the perspective of those involved in deviant behavior (i.e., the perpetrator or victim). Taking -Kelly, 2005). In this respect, our results likely represent a simplified thirdparty response.…”
Section: Discussionmentioning
confidence: 72%
“…Although researchers have developed an understanding of the individual and situational factors that predict whether individuals will engage in workplace deviance (e.g., Barling, Dupré, & Kelloway, 2009) as well as the associated consequences (e.g., Aquino & Thau, 2009), comparatively less attention has been devoted to investigating third parties' reactions to the deviant behavior of others. However, given that the majority of incidents of workplace mistreatment occur in the presence of others (Glomb, 2002), understanding third-party reactions to such deviant acts is particularly important, as the reactions of these individuals can have significant implications for the perpetrator as well as the victim (Bowes-Sperry & O'Leary-Kelly, 2005). For example, third parties could provide advice and social support to the victim, or even decide to intervene to stop the perpetrator (O'Reilly & Aquino, 2011).…”
Section: Reactions To Workplace Deviancementioning
confidence: 99%
“…A recent study found that having post-training activities (e.g., rewards for applying training to the job, refresher course) after sexual harassment training was signifi cantly related to a reduction in sexual harassment complaints (Perry et al 2010 ). Bowes-Sperry and O'Leary-Kelly ( 2005 ) explain that bystander intervention training can be important for stopping sexual harassment and providing support to victims.…”
Section: Sexual Harassment Training Programsmentioning
confidence: 97%
“…In fact, Knapp et al (1997) reported that just over 1 in 10 persons who are harassed report that incident. In these situations, observers' behavioral responses to the sexual harassment of coworkers could be of great help in deterring this unethical behavior (Bowes-Sperry and Powell 1999;Bowes-Sperry and O'Leary-Kelly 2005;Roumeliotis and Kleiner 2005).…”
Section: Behavioral Responsesmentioning
confidence: 99%